Analisa Pengaruh Intellectual Capital Terhadap Profitabilitas Dan Produktivitas Pada Sektor Perbankan Syariah Indonesia Cabang Kota Tangerang - Sendy Zul Friandi; Imam Nugroho Akbar (UNIVERSITAS RAHARJA, 2018)
This study aims to determine theinfluence of intellectual capital to profitability and productivity on islamic banking in indonesia. Data obtained as many as 10 islamic banking City of Tangerang with the period from 2015 to 2017 and linked to the 3 variables of the study, namely: 1 independent variables: intellectual capital and 2 dependent variables: profitability and productivity. Data analysis methods used are test for normality, multicollinearity test, heteroskedastisitas test, autocorrelation test, a test of determination, t test and F test. The results showed that: (1) variable VACA,VAHU, STVA does not affect the profitability (ROA), (2) variable VAIC simultaneosly affects significant impact on profitability (ROA) , and (3) variable VACA, VAHU, STVA and VAIC simultaneosly affects significant impact on productivity (ATO).